Ellen R. Grass Lecture: Extraordinary EEG. - Tatum, William O. (Neurodiagnostic Journal, 2014)
The electroencephalogram (EEG) is a unique measure of the electrical function of the brain. Cerebral sources of EEG potentials expressed by the human brain have been recorded on the surface of the scalp for almost 100 years. With the advances in digital technology, present day EEG has evolved to include specialized techniques that offer new capabilities never realized before. Refined intracranial recording techniques and multi-channel systems now permit access to regions of the brain that have previously been off limits to conventional EEG recording. Extraordinary biorhythms beyond 1 to 35 Hz that have been typically used in routine EEG are now exploring extreme band-widths that may disclose epileptogenic regions and their yield causative networks involved in generating seizures. These spectral frequencies ranging from infraslow activity to high frequency oscillations have far reaching implications for people with uncontrolled seizures. Micm-EEG recordings are now shedding light on electrophysiological recordings of single columns of neuronal activity in clinical research expanding our understanding of epilepsy to the cellular level. Beyond the routine application of EEG analyzed for clinical use, special EEG techniques now provide a window to reveal detailed information about the seizure onset zone in patients with epilepsy, as well as advance our understanding of the functional processes of the brain itself. These breakthroughs will allow EEG-based treatment alternatives.